Factors that Influence Purchasing Decicions of Asian Chinese Food Coffee and Resto in Bogor - agus salim; Tara Novia Santang (Perbanas Institute, 2022)
This purpose of this research was to identify and analyze the Influence of services quality, price and product quality on the purchase decision Asian Chinese food coffee and resto. The method that used in the research was using quantitative descriptive analysis with likert scale as measuring instrument. The population in this study is the people who have purchased Asian Chinese food coffee and resto, while the sample number is 75 people. The results showed that: (1)The higher the level of quality of service provided, the higher the consumer purchasing decision. (2) The higher the price level of the product given, the higher the consumer purchasing decision. (3) The higher the level of quality of products provided, the higher the level of consumer purchasing decisions. Keywords: Services Quality, Price, Product Quality, Purchase Decision, and Chinese food.